Knowledge About COVID-19 Symptoms, Transmission, and Prevention: The Relationship With Cognitive Status in Older Adults. (September 2022) - Goldstein, Felicia C.; Saurman, Jessica L.; Rodriguez, Amy D.; Vickers, Kayci L.
Objective: Advanced age poses an increased risk for cognitive impairment, and therefore, poor knowledge regarding the risks associated with COVID-19 may confer vulnerability. We administered a COVID-19 Knowledge Questionnaire to older persons to evaluate the association between knowledge regarding public health recommendations, and cognitive status as measured by the Montreal Cognitive Assessment (MoCA).Method: Ninety-nine participants completed a 22-item questionnaire about COVID-19 symptoms, risks, and protective strategies, and they also completed the MoCA. Associations between knowledge and cognitive status were examined via Spearman correlations.Results: The mean (SD) age of participants was 72.6 (7.6) years, and MoCA scores averaged 23.4 (4.5) points. Higher MoCA total scores were significantly ( p < .001) correlated with a greater number of correct questionnaire responses. Higher Orientation and Memory Index scores were moderately associated with an increased number of correct responses ( p < .001), with the Executive Index exhibiting a significant albeit weaker association. MoCA Index scores assessing attention, language, and visuospatial functioning were not significantly associated with COVID-19 knowledge.Conclusions: Given the rapid transmission rate of the SARS CoV-2 infections, COVID knowledge lapses will likely have deleterious repercussions. Public health messages should ensure effective acquisition and retention of COVID specific information, especially in cognitively compromised older adults.